Examining The Effects of Islamic Ethical Values, Environmental Concern, and Social Norm on Green Halal Purchase Intention: The Mediating Role of Consumer Trust - Muhammad Abduh; Titania Mukti; Elif Pardiansyah (Economics and Business Journal (ECBIS), 2026)
The convergence between sustainability and halal consumption practices has led to a surge of interest in identifying variables influencing consumer behavior towards purchasing eco-friendly and sustainable halal goods. This paper examines the effects of Islamic ethics, environmental consciousness, and social norms on the purchase intention of eco-friendly and sustainable halal products, considering the moderating role of consumer trust. Four hundred and twelve participants among Muslims participated in the study, and their data were analyzed using partial least squares structural equation modeling. The proposed model had good explanatory power as it was able to explain 68.4% and 59.7% of the variances in green halal purchase intention (R² = 0.684) and consumer trust (R² = 0.597), respectively. Results of this study indicate that Islamic ethics (β = 0.31, p < 0.001), environmental consciousness (β = 0.27, p < 0.001), and social norms (β = 0.22, p < 0.01) positively influenced consumer trust. Moreover, consumer trust significantly and positively impacted green halal purchase intention (β = 0.45, p < 0.001). The mediation analyses reveal that consumer trust partly mediates the effect of Islamic ethical values, environment, and social norms on green halal purchase intention. Out of all the antecedents tested, Islamic ethical values have been found to be the most effective determinant of green halal purchase intention. It can thus be concluded that the purchase intention for green halal products increases significantly if the customers perceive these products as being consistent with Islamic moral standards, sustainable for the environment, and approved by society, especially where the issue of consumer trust is involved. This research has contributed significantly to the extant literature by showing how trust acts as an important bridge between the antecedents of green halal purchase intention and the actual intention to purchase.